The Design Idea and its Application in the Inner Space (Refreshments Shops as Sample) - Naderah Abdul Razzaq Ghazal (Journal of Techniques)
The inner or architect faces difficulty in choosing his applicable design, so that the research presents a study based on scientific and practical components to find out a design idea as an objective study and the mechanisms of application by utilizing modern technology and the products of the digital world to achieve a sustainable and balanced environment participates in upgrading the inner designs so it comes with the concept of the design idea and means of cognitive processing that take part in its application in real life to reach the title of the research “The design idea and its application in the inner space ‘’ the study as a necessity resulted from a need to increase design awareness in finding out a link between the application of the design idea and precept it.